Komunikasi Terapeutik Perawat dengan Kepatuhan Minum Obat Hipertensi - Lahay, Maryam K.; Monayo, Edwina R; Azis, Moh. Nisyar Sy. Abd. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the relationship between nurses’ therapeutic communication and medication adherence among elderly patients with hypertension. A cross-sectional design was employed using an accidental sampling technique involving 47 elderly respondents. The results showed a significant relationship between nurses’ therapeutic communication and antihypertensive medication adherence among the elderly (p-value = 0.000). In conclusion, higher levels of nurses’ therapeutic communication are associated with greater medication adherence among elderly patients. Keywords: Therapeutic Communication of Nurses, Medication Adherence, Elderly